Pengaruh Pemberian Tahu-Tempe Terhadap Peningkatan Berat Badan Bayi Penderita Gizi Buruk di Kabupaten Jember - Ardiana, Anisah; Purwandari, Retno (Jurusan Keperawatan FIKES UNSOED, 2011)
The national development programme have made since 2000, focused in effort to increase people nutrition. Malnutrition not only stigma that make afraid, this problem connected with the effects of family or country economic. Malnutrition is potentially causing of poorness caused from lower quality of productivity and human resource. Intake of protein become one of alternative to reduce malnutrition cases. Protein is provided in animal and nabati protein. Tahu and tempe are Indonesian traditional food that contain nabati protein. This research used true experimental research with Ã¢â‚¬Å“pretest-postest designÃ¢â‚¬Â with one intervention. The subject of this research is children under 5 years old with malnutrition in Kalisat Jember. Technical sampling used in this research is purposive sampling while data analysis used paired sample t-test.The experiment group looks increase body weight, with means value 0.4438 after got intervention (additional food tahu-tempe 200 gr per day). The control group have changing weight with means value 0.1250. Based on paired sample t-test with confidence degree 95 %, the t-tabel value 2.131 and t-count value 2.253, with p-value 0.040 (ÃŽÂ±:0.050). p-value less than the ÃŽÂ±- value, statistically, it means that Ho refused. So it means that there is an influence of giving additional food (tahu-tempe) to increasing body weight for malnutrition. This research conclude that tahu-tempe have influence to increasing body weight for children under 5 years old with malnutrition in Jember. Etiology of malnutrition are poorness and lower of mother knowledge about nutrition.